Cyfryzacja administracji na przykładzie projektowanych zmian w przepisach o cmentarzach i chowaniu zmarłych .......... 253 - Ruczkowski, Piotr (E-administracja: Wyzwania dla cyfrowych usług publicznych w Unii Europejskiej, 2024)
ADMINISTRATIVE DIGITALISATION AS EXEMPLIFIED BY THE DRAFT AMENDMENTS TO THE LEGAL PROVISIONS ON CEMETERIES AND BURIAL OF THE DEADThe existing provisions of law on cemeteries and burial of the dead, although repeatedly amended, do not meet not only the contemporary challenges concerning political, cultural or lifestyle changes, but also appear to be archaic in view of technological transformation, especially accelerating digitalisation of social life and state administration processes. Therefore, it is necessary to prepare new legal regulations that will respond as effectively as possible to the challenges generated in the area of funeral law. In particular, many changes are to be made in the area of digitalisation. Among the proposed solutions, we should mention an electronic death card, an electronic stillbirth card, electronic processing and transfer of data to registries, the creation of central and publicly accessible databases of graves and resting places and a cemetery register.